Are we spending too much on HIV? - de Lay, Paul (BMJ Publishing Group Ltd., 2007)
Billions of pounds are being spent on the fight against AIDS in developing countries. Roger England believes that much of the money could be better used elsewhere, whereas Paul de Lay and colleagues argue that current spending is not enough